REPRESENTAÇÕES SOCIAIS DOS ENFERMEIROS DA ESTRATÉGIA SAÚDE DA FAMÍLIA SOBRE O TRATAMENTO DIRETAMENTE OBSERVADO (TDO) DA TUBERCULOSE - Oliveira, Poliana Soares de (2014)
The Directly Observed Treatment(DOT) isconsidered a milestonefor global TB control, which adapted to the conditionsof each localitycan contributeto achieving theglobal targetsforTB control,which are: to detect 70% of cases and curing 85% of these. Thestrategy includesinits operation, which emphasizefive elements: political commitmentgovernment; detection ofcasesfrom thesmear; increasein cure rates; regular supplyof drugs andnotification system forcases(GONZALES, etal, 2008;). TheMS(BRAZIL, 2011b) highlightsthat the roleof the nursehas a fundamentalroleto ensuresupervision ofallTDO, ensuring patient adherenceto asuccessful treatment. However, we realize regardingthe roleof nurses inTDO, fromempirical observationsof practice andgroup discussionsofwelfareresearch amongnursesand researchersin the area, some limitationsto operationalizethe strategy, highlightedthe importancegivenoversightof decision-medicinesto the detrimentof otheractions thatare partof theTDO. The object of this researchare the socialrepresentations of theTDOfor nurses FHS, theoretically basedTheoryof Social RepresentationsofSergeMoscovici. To identify the social representationsof nursesofthe Family Health Strategy(FHS) on the Directly Observed Treatment(DOT) for tuberculosis. This isa representationalstudy, qualitativeapproach, performedin health facilitiesof the family whomade operational ODD, in SãoLuís-MA. The subjects wereall nurseswho workedwith ODD strategyin theseunits. Wereused to collectdatatotestFree Word Association, a semi-structured interview and a tooltoidentify sociodemographicdata.The analysis was performedusing theEVOCand techniqueof content analysis. The researchcomplied with Resolution466/12of the NationalHealth Council. When evaluatingevokedwordsand speechespresentedby the research subjects, there was a clear relationshipbetween them, validating the results obtainedwithTALP. In the speechdeliveredby nurses, it was observedthatthe coreelementswere highlightedin the speechesof the elderly. The structureof the representationswasorganizedas follows: corecomposed of thetermsmedication, cure, care and supervision; elementsof thefirst peripherycomposed ofdedication,bonding,adhesion andcommunity health workers; elements of the secondperipherycomposed of thetermsand preventionorientationandcontrast elementswerefoundlayingand rejection. We found that, in the interviewwith the nurseson theTDO, the subjects showedrepresentations basedon several factorsrelatedto feelings,attitudes anddaily practicesof amedicalmodel of health-dressing, focused moreon theindividual thanthe collective, moreon healingthatin care. It was foundthat theunderstanding ofODDis presentedtothe nurseasa therapeuticdose of the medicationthrough theaction,as a guaranteeof cure, which actually representsan understandingthatdistance from thetrue purposeand aims of theTDOstrategy, causing it to beoperationalizedin error, in disagreementwith the pillarsthat govern itssustainabilityas the beststrategy to combatTB.